2016
DOI: 10.1371/journal.pone.0117805
|View full text |Cite
|
Sign up to set email alerts
|

New Introductions, Spread of Existing Matrilines, and High Rates of Pyrethroid Resistance Result in Chronic Infestations of Bed Bugs (Cimex lectularius L.) in Lower-Income Housing

Abstract: Infestations of the common bed bug (Cimex lectularius L.) have increased substantially in the United States in the past 10–15 years. The housing authority in Harrisonburg, Virginia, conducts heat-treatments after bed bugs are detected in a lower-income housing complex, by treating each infested unit at 60°C for 4–6 hours. However, a high frequency of recurrent infestations called into question the efficacy of this strategy. Genetic analysis using Bayesian clustering of polymorphic microsatellite loci from 123 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…The present survey confirms the perception that bed bugs are a nuisance that is growing fast. This increase has already been confirmed in North America, Europe and Australia [ 8 , 15 , 17 ]. In order to document it in metropolitan France, we could take inspiration from the model adopted in Montreal ( Règlement 03-096 sur la salubrité , l’entretien et la sécurité des logements , Ville de Montréal, 2012), for example, with an obligation for insect control companies to declare their interventions to the municipality concerned, providing simple information such as the date, the town, the neighbourhood and the semi-quantitative infestation level.…”
Section: Discussionmentioning
confidence: 58%
“…The present survey confirms the perception that bed bugs are a nuisance that is growing fast. This increase has already been confirmed in North America, Europe and Australia [ 8 , 15 , 17 ]. In order to document it in metropolitan France, we could take inspiration from the model adopted in Montreal ( Règlement 03-096 sur la salubrité , l’entretien et la sécurité des logements , Ville de Montréal, 2012), for example, with an obligation for insect control companies to declare their interventions to the municipality concerned, providing simple information such as the date, the town, the neighbourhood and the semi-quantitative infestation level.…”
Section: Discussionmentioning
confidence: 58%
“…Gellatly et al, (2016) showed that in the human head louse Pediculus capitis, a high frequency of kdr-type mutations lowers the effectiveness of permethrin formulations. Moreover, Raab et al, (2016) explained that in a building infested with the bed bug Cimex lectularius, there were 8 genetic clusters with no gene flow between them, and 40% of the insects were homozygous for two concomitant kdr mutations, responsible for the decrease in effectiveness of the insecticide.…”
Section: Target-site Insensitivitymentioning
confidence: 99%
“…If lethal temperatures are not achieved, bed bugs may detect and respond behaviorally to sublethally heated areas by fleeing to cooler areas such as wall voids, deep within furniture, or in neighboring unheated apartments [18–20]. Bed bugs stunned by sublethal heat exposure could fall into protected areas and recover afterwards [21].…”
Section: Introductionmentioning
confidence: 99%
“…Bed bugs stunned by sublethal heat exposure could fall into protected areas and recover afterwards [21]. In one case, it was observed that bed bugs escaped from a heat-treated apartment to an adjacent unheated unit to avoid heat exposure [20]. Loudon [22] reported that a single bed bug moved from the heated exterior to the cooler interior of a luggage case in an attempt to escape lethal heat exposure.…”
Section: Introductionmentioning
confidence: 99%